PENGARUH BRAND IMAGE DAN ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP CUSTOMER SATISFACTION PADA PRODUK KOSMETIK SOMETHINC - Fitri Annisa Zanova; Annur Fitri Hayati (LP2M Universitas Bina Bangsa, 2024)
This study aims to obtain an overview of the influence of brand image and electronic word of mouth (e-wom) simultaneously on consumer satisfaction in several products. This study uses a type of quantitative research with a type of causal research. The population of this study is Padang State University students who use several products and samples of 97 respondents using a non-probability sampling technique of purposive sampling. The results of the research on the Influence of Brand Image and Electronic Word of Mouth (E-Wom) on Customer Satisfaction of Sometinc Cosmetic Products. In Sometinc Products, 1) The Brand Image of Sometinc cosmetic products is considered more positive and good by Padang State University students. 2) E-Wom Sometinc cosmetic products have a great influence on the purchase of products by students of Padang State University. 3) Consumer satisfaction with Sometinc cosmetic products, especially Padang State University students, is quite good